CLINICAL PRESENTATIONS OF NEPHROTIC SYNDROME IN PATIENTS OF A TERTIARY CARE HOSPITAL AT PESHAWAR - Din, Najam -ud-; Khan, Ahmad Zeb; Shah, Syed Javed Hussain; Anwar, Nisar; Hakeem, Fuad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Nephrotic syndrome (NS) is manifested by presence of pitting oedema, profound proteinuria in excess of 3.5 g/day, serum albumin levels of less than 3.0 g/dL and hypercholesterolemia. This study was conducted to determine the frequency and clinical presentation of nephrotic syndrome in patients coming to a tertiary care hospital. Methods: This cross-sectional study was done from March to November, 2012 (for 9 months). Patients with complaints of peri-orbital or generalized swelling, and proteinuria on urine examination were included in the study through emergency or out-patient department. Results: Out of 360 suspected cases, nephrotic syndrome was found with a frequency of 67.05%. Among these patients, 69.55% were male and 30.45% female. Majority (65.85%) were between 41-60 years with mean age of 40.36±15.93 years. All (100%) patients had oedema, 43.20% had oliguria, 17.28% presented with abdominal tenderness, 15.22% patients had fever, 13.16% showed hematuria, 10.28% patients had uraemia and 2.5% of the patients had thrombosis. The majority of patients (56.80%) were diabetic, and 43.20% patients had hypertension. In 23.86% patient's high blood urea alone was recorded and 17.28% showed high serum creatinine along with raised blood urea. Rest of patients had normal renal function at the time of presentation. Conclusion: Frequency of nephrotic syndrome was 67.05%. Among these majorities were males. Oedema was the commonest presenting complaint while oliguria, abdominal tenderness, fever, hematuria, uraemia and thrombosis were found in descending orders. Diabetes mellitus was leading cause in majority of patients, followed by hypertension, high blood urea, and high serum creatinine. Keyword: Nephrotic syndrome; presenting features; diabetes mellitus; hypertension